Performan Ayam Broiler yang diberi Ransum Mengandung Potassium Diformate Sebagai Pengganti Flavomycin - Nahrowi Ramli; Dwi Margi Suci; S. Sunarto; C. Nugraheni; A. Yulifah; A. Sofyan (Agricultural Faculty, 2008)
Performance of broilers fed diets containing potassium diformate to replace flavomycinABSTRACT. The aim of this research was to study the effect of potassium-diformate (PD) on broiler performance. One hundred and twenty old chicks of Cobb strain were divided into fifteen groups and feed one of five treatments, namely: P1 (control diet), P2 (P1 + 0,5%PD), P3(P1 + 1%PD), P4 (P1 + 1,5%PD) and P5 (P1 + antibiotic). Data from Completely Randomized Design were analyzed by ANOVA and any significant among them were used contrast orthogonal test. Treatments did not impact on feed consumption, mortality and percentage of viscera, but the groups treated with 1 and 1.5% PD and flavomicyne antibiotic had significant improvement on body weight gain (P0.169) and feed efficiency (P0.05). It is concluded that addition of 1-1.5% potassium-diformate in the broilers diet could improve feed efficiency and replace flavomycine antibiotic as growth promotors without influencing the performance of viscera.